The qT spectrum of the Higgs boson at the LHC in QCD perturbation theory - Bozzi, G. (2003)
We consider the transverse-momentum (qT) distribution of Higgs bosons produced at hadron colliders. We use a formalism that uniformly treats both the small-qT and large-qT regions in QCD perturbation theory. At small qT (qT ≪ MH, MH being the mass of the Higgs boson), we implement an all-order resummation of logarithmically-enhanced contributions up to next-to-next-to-leading logarithmic accuracy. At large qT (qT ≳ MH), we use fixed-order perturbation theory up to next-to-leading order. The resummed and fixed-order approaches are consistently matched by avoiding double-counting in the intermediate-qT region. In this region, the introduction of unjustified higher-order terms is avoided by imposing unitarity constraints, so that the integral of the qT spectrum exactly reproduces the perturbative result for the total cross section up to next-to-next-to-leading order. Numerical results at the LHC are presented. These show that the main features of the qT distribution are quite stable with respect to perturbative QCD uncertainties. © 2003 Elsevier Science B.V. All rights reserved.